Factors influencing transit fatigue of seamless pipes - Kunert, Hernan Guillermo (2005)
Full‐scale fatigue tests simulating real pipe stock conditions in ships were carried out in order to reproduce failures of seamless pipes due to fatigue crack growth during shipping. Simple mechanical analyses were then used to assess the factors that influence transit fatigue. As seen in several actual failures, fatigue cracks were found to propagate from both sides of the pipe wall. It is possible to have transit fatigue (TF) when piling up a few pipes for transportation, if there is previous plastic indentation. Susceptibility to TF was found to be independent of the nature of discontinuities in the surfaces of the pipes. Precautions to reduce the probability of TF in sea shipment include preventing plastic indentation of the pipes and storing stiffer pipes in the bottom part of the hold.